IMPLEMENTATION OF PRICE REASONABILITY AND CONSUMER PURCHASE INTEREST AT BERYL'S CHOCOLATE KINGDOM MALAYSIA STORE (Case Study on STIE Sutaatmadja Students’ Participating in KKL 2019) - Ghina Salisatun Mubarokah; Ririn Megasari; Bismantara Bismantara (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2021)
This study aims to determine the implementation of fairness of the price and buying interest. This type of research used quantitative descriptive, this research was conducted on august 20-22,2019 with the subject of this study were the KKL students STIE Sutaatmadja Subang who visited Malaysia as cunsumers in Beryl's Chocolate Kingdom Store in Malaysia. Thi study used primary & secondary data, the instruments in this study are questionnaries. Data collection techniques used are questionnaires distributed to 103 respondents, observation and literature study. While the data analysis through sample data slot777 using sample random sampling techniques. The result of observatonal studies show that  the fairness of the prices applied in the Beryl’s Chocolate Kingdom store in Malaysia is based on indicators of the price awareness which include affordability, price sustability of prices with brandsm and price saticfaction. Both in terms of the taste of the price and the quality of the products presented, while the result of costumer perceptions about the offer price offered by the Beryl’s Chocolate Kingdom Store in Malaysia something with consumer purchasing power even though there are some who say it is not in accordance with purchasing power of consumers.